Cholesterol esterification rate in plasma depleted of very low and low density lipoproteins is controlled by the proportion of HDL2 and HDL3 subclasses: study in hypertensive and normal middle-aged and septuagenarian men - Dobiasova, M; Stribrna, J; Pritchard, P H; Frohlich, J J (Journal of lipid research, 1992)
The relationship between the fractional rate of cholesterol esterification (FERHDL) in very low density lipoprotein (VLDL)- and low density lipoprotein (LDL)-depleted plasma and the particle size distribution of high density lipoproteins (HDL) were studied in: a) a control group of 9 apparently healthy men (42 +/- 11 years); b) 15 septuagenarians (76 +/- 6 years) who had no clinical signs of coronary artery disease; and c) 32 outpatients with essential hypertension of different stages of severity (51 +/- 10 years). There were small differences between the groups with respect to their plasma total and HDL-cholesterol and plasma triglyceride levels. However, there was a highly significant increase in FERHDL in patients with hypertension compared to control and older men. The HDL of hypertensive patients had a markedly increased relative content of HDL3b, while their HDL2b fraction was reduced by over 50% compared to the other groups. Overall, there was a strong positive correlation between FERHDL and HDL3b (r = 0.89; P less than 0.001) and a negative correlation between FERHDL and HDL2b (r = -0.61; P less than 0.001) and HDL3a (r = -0.77; P less than 0.001). These findings confirm our previous conclusions that FERHDL reflects the relative HDL subclass distribution. In addition, we demonstrate that FERHDL is increased in hypertensive male subjects regardless of the stage of hypertension, i.e., whether or not organic lesions have already become manifest (stage III and stages I plus II, respectively).
Keywords: Electrophoresis, Polyacrylamide Gel; Cholesterol; Humans; elektroforéza v polyakrylamidovém gelu; cholesterol; lipoproteiny VLDL; lidé středního věku; Hypertension; Lipoproteins, HDL; Aged; dospělí; věkové faktory; senioři; lidé; lipoproteiny HDL; Esterification; Adult; Lipoproteins, VLDL; lipoproteiny LDL; Male; Middle Aged; hypertenze; Age Factors; Lipoproteins, LDL; mužské pohlaví; esterifikace